Passenger Lymphocyte Syndrome after Liver Transplantation: A Cause of Hemolytic Anemia - Rocha, Diana Isabel; Ferreira, Sofia Moreira; Antunes, Marika Bini; Miranda, Helena Pessegueiro (Acta Médica Portuguesa, 2022)
N/a.